Body image concern and treatment outcomes in adolescents with anorexia nervosa. Issue 5 (31st January 2019) - Calugi, Simona; Dalle Grave, Riccardo
Abstract: Objective: To ascertain the role of baseline measures of body‐image concern (BIC) in changes in body mass index (BMI) centile and psychopathological outcomes associated with intensive enhanced cognitive behavioral therapy (CBT‐E) in adolescents with anorexia nervosa (AN). Method: The BMI centile of 62 adolescent patients with AN was recorded at four time‐points over 12 months, and Eating Disorder Examination interview (EDE) and Brief Symptom Inventory (BSI) scores, were recorded at admission and discharge from CBT‐E. Changes in three BIC components, namely "Preoccupation with shape/weight", "Fear of weight gain" and "Feeling fat", were assessed at admission and discharge. Results: CBT‐E was associated with a significant improvement in outcome variables and BIC components. Among completers, 96.4% reached an end‐of treatment BMI centile corresponding to a BMI ≥ 18.5 at 18 years, which fell slightly to 78.7% and 80.4% at 6‐ and 12‐month follow‐ups, respectively. Baseline "Preoccupation with shape/weight" and "Feeling fat" predicted improvement in BMI centile over time, and all three baseline BIC components independently predicted end‐of‐treatment EDE Eating Concern subscale score. Baseline "Feeling fat" also predicted end‐of‐treatment EDE Dietary Restraint subscale and BSI scores. Discussion: These findings highlight the importance of assessing and addressing body image when managing adolescent patients with AN.